Nonprofit management research: teams, design and recent topic trends - Santos, Márcia Rafaela Cadete dos; Laureano, Raul Manuel Silva; Abreu, Madalena Eça de (Contemporary Issues in Tourism & Management Studies, 2014)
Periodically, for scholar purposes, an overview on the actual publications about a research topic is essential when starting finding gaps and identifying widely covered issues. This paper reviews the nonprofit management research published in one top nonprofit journal in 2013. The main goal of this paper was to review the recent literature on nonprofit field and identify significant trends regarding several dimensions. A total of 22 articles are reviewed and classified based on variables which allow to present results about research team, sample, methodology and significant findings. The analysis of recent scientific articles revealed that a large number of research projects are focused on identifying approaches leading to sustainability of the nonprofit sector. This paper provides an essential contribution to research projects which aim to understand to what extent current research trends are achieving nonprofit needs.